Implementasi Standar Pengelolaan Usahatani Kapulaga Pada Lahan Agroforestri di Kabupaten Tasikmalaya - Nuryati, Rina; Faqihuddin; Asri Siti Fatimah; Ruslan, Januar Arifin (Jurnal Pengabdian dan Pemberdayaan Masyarakat Inovatif, 2022)
Practice of cultivating agroforestry plants is well known to the people of Tasikmalaya Regency is Cardamom Plants. The cultivation of this plant is faced with low quality and production. This is influenced by management which is still simple. This service activity is expected to be able to increase the ability to manage cardamom farming for farmers. This service activity using counseling methods and discussions with farmers regarding the management of cardamom farming according to standards. evaluation of service activity based on the farmers' response to this activity. From this service activity, it shows that the farmers are enthusiastic and give a satisfied response. Farmers are able to know the management that should be at every stage of cardamom farming activities.